2019
DOI: 10.12707/riv19023
|View full text |Cite
|
Sign up to set email alerts
|

When long-term care comes to an end: informal caregivers’ perspectives on patient discharge

Abstract: Background: The purpose of long-term integrated care units is the readaptation and reintegration into family and social life. Objective: To understand informal caregivers' perspectives on the discharge of their relatives with dementia from long-term care facilities. Methodology: Fifteen caregivers (mean age of 60 years) were interviewed, and data were qualitatively analyzed using NVivo. Results: Despite the concern and fear about discharge, most participants did not take any action. When questioned about what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Added to this is the fact that caregivers sometimes neglect their own health and self-care to care for their children. These factors in association can cause, in the short and medium term, overload and/or stress that will influence the quality of care provided and the perception of quality of life [10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Added to this is the fact that caregivers sometimes neglect their own health and self-care to care for their children. These factors in association can cause, in the short and medium term, overload and/or stress that will influence the quality of care provided and the perception of quality of life [10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…The emotional needs relate to the feeling of discomfort of the person in a specific moment of his/her life to cope with the illness situation and its repercussions and with the behavior of the sick person. According to the study conducted by Carvalho, Araújo, and Veríssimo (2019), the family experiences fear, sadness, insecurity, and difficulty in imagining a future for the sick person and for himself/herself. Thus, it is important to identify strategies that allow the family to deal daily with the person with NCD through training, information, support, and a more individualized service in the provision of health care and social support.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they need to adapt to the reality they experience, requiring dedication and, at times, exclusive availability. In this sense, an investigation identified that caring parents experience overload, stress, anxiety, in addition to different degrees of depression (8)(9) . Despite this, with the benefits of using the feeding tube, such as weight gain and adequate child development, negative reactions and feelings are minimized, thus evidencing the use of situational coping or coping strategies (7) .…”
Section: Religious/spiritual Coping In Informal Caregivers Of Children With Cleft Lip And/or Dysphagic Palatementioning
confidence: 99%
“…Thus, the demand for care linked to the diagnosis of a chronic situation can lead to drastic physical and emotional symptoms, which may negatively influence behavior and adaptation, also affecting the quality of care provided (8)(9) . Thus, adaptations are needed so that they experience this period in a less painful way, that is, it is necessary to establish or develop modalities of situational coping, referred to as coping.…”
Section: Introductionmentioning
confidence: 99%